Wahana Wisata di Negeri Syariat (Implementasi Nilai Syariat Islam pada Wahana Impian Malaka, Aceh Besar) - Aini, Zahraton; Arisva, Vatta (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
This article aim to explain the management of Wahana Impian Malaka tourism based on Islamic Sharia and to describe the obstacles faced by Wahana Impian Malaka managers in conforming to Islamic Sharia. This research uses a qualitative descriptive approach (field research), with data collection techniques using observation, interviews and documentation. The results of this study indicate that the management mechanism at Wahana Impian Malaka Tourism in general has implemented Islamic Sharia rules, such as: turning off live music when prayer time comes, providing facilities for prayer services, separating changing rooms to women and men, selling of halal food, and wearing modest clothing; the female administrators wear headscarves and the male managers also wear dress politely and neatly. Obstacles and challenges faced by both the manager and the surrounding community in implementing Islamic Sharia-based rules are: non-separated male and female pools, no punishment by managers for tourists who violate Islamic Sharia rules, lack of socialization from management and government and the lack of concern from the local community in the implementation of Islamic Sharia.